Emerging Sustainable Marketing Practices in International New Ventures : The Role of Digital Technologies and Strategy-in-Practice - Sohaib, Mehr (My University, 2026)
This master’s thesis investigates how sustainable international marketing practices develop in International New Ventures and examines the role digital technologies play in this process. As global pressures for environmental and social responsibility intensify alongside rapid digital transformation, understanding how young, resource-constrained firms integrate sustainability into their international marketing activities has become increasingly important. While existing research has examined sustainability, digitalization, and strategic practice in isolation, limited attention has been given to the micro-level processes through which these elements combine in the daily work of internationally operating entrepreneurial firms. The study addresses this gap by asking how sustainable international marketing practices develop in International New Ventures and what role digital technologies play in this process. Drawing on the Resource-Based View, Dynamic Capabilities perspective, and Strategy-as-Practice approach, a qualitative research design was adopted. Four semi-structured interviews were conducted with managers and entrepreneurs from diverse industry contexts. The interview data were analyzed using thematic analysis, facilitated by NVivo software. The findings reveal that sustainability integration follows a predominantly reactive pathway, triggered by external pressures from international customers and regulatory requirements, particularly in advanced European markets. Over time, practices evolve from reactive compliance to strategic integration, characterized by increasing intentionality and embeddedness in organizational routines. Leadership commitment emerges as the most critical internal enabler, while customers and regulations constitute the primary external drivers. Digital technologies play a transformative role, enabling data-driven decision-making, enhancing transparency, and accelerating response times across international markets. However, digitalization also introduces new challenges related to data privacy, cost, and measurement limitations. The Strategy-as-Practice lens reveals that sustainable marketing is accomplished through everyday routines, cross-country coordination, and ongoing sensemaking work. Strategic outcomes include enhanced legitimacy, market differentiation, strengthened stakeholder relationships, and international growth. This study contributes to international business and sustainability literature by offering a micro-level understanding of how sustainable marketing practices are enacted in International New Ventures. For practitioners, the findings underscore the importance of leadership commitment, gradual capability development, and strategic investment in digital tools.
Keywords: digitalisation; marketing; sustainable development; international market; internationalisation; international corporations; enterprises; environmental responsibility; marketing communication; marketing research; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business